The influence of coordination on the attention stability of children with different nervous system typologie - Polevoy, Georgiy Georgievich (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The aim of the study is to define the influence of coordination abilities on attention stability development in first graders with different strengths of nervous system. Sixty 7- to 8-year-old schoolchildren from a usual comprehensive school participated in the research. Prior to the research, all children had been differentiated on equal 3 groups. The pedagogical experiment continued 7 months. During research there were changes in the groups. In the group KG, in the Shuttle run test, indicators have worsened from 10,3±0,6 s. to 10,4±0,6 s. (P>0,05), and in the methodic Bourdon Test indicators have worsened on 0,1 p. (P>0,05). In the group EG-2, in which schoolchildren were engaged taking into account the nervous system typology, there were considerable and positive changes. In the Shuttle run test indicators have improved from 10,3±0,6 s. to 9,7±0,5 s. (P<0,05), and in the methodic Bourdon Test indicators have improved on 1,4 p. (P<0,05). If the differentiated approach based on the typology is used, the indicators of movement coordination and attention stability will improve considerably during training.